There's Something I've Been Dying to Tell You - Bellingham, Lynda (London Coronet, 2014)
In 2013 Lynda Bellingham was diagnosed with cancer. Having kept the details of her illness private, now for the very first time Lynda talks with beautiful poignancy about her life since her diagnosis, her family and how together they came to terms with a future they hadn't planned. Having been told that she only has a matter of months left to live and writing this in what will sadly be her final days, There's Something I've Been Dying To Tell You is a brave and brutally honest memoir and yet Lynda also manages to spread her infectious warmth and humour, bringing light to a very dark time. Woven into this very moving and brave story are extraordinary, colourful tales of her acting and family life that will enlighten and entertain as well as the journey that Lynda has taken to find the family of her birth father having already suffered heartache in her search for her birth mother. In the search for her father's family, Lynda finds a family with a history in entertainment showing that acting was always in the blood. Lynda Bellingham is a tremendously gifted storyteller with a rich collection of tales of love, loss and laughter and this book brings her kind heart, courage and emotion to the page in vivid detail. Lynda's story is an affecting and at times heart-breaking one but it is so often laugh-out-loud too and ultimately the way Lynda tells her life story will serve as a great inspiration.
Include Color Illustration
Keywords: Bellingham, Lynda. -- Cancer -- Patients -- Family relationships. -- Colon (Anatomy) -- Cancer -- Patients